MULTIMEDIA LEARNING FOR WUDHU AND SHOLAT PROCEDURES ANDROID BASED AT TK PERTIWI 01 SERANG - Widiastuti Widiastuti; Siti Masturoh; Ahmad Hafidzul Kahfi; M Rangga Ramadhan Saelan; Ridan Nurfalah; Muhammad Hilman Fakhriza (Jurnal Techno Nusa Mandiri, 2020)
Wudhu is one way to purify oneself from uncleanness and suffering. Performing ablution perfectly in accordance with Islamic Shari'a is the key to receiving prayer. The introduction of religious activities such as ablution and prayer from an early age is considered necessary. Learning ablution and prayer is usually done by parents repeatedly and by example. In one study, 8 out of 10 children aged 5-6 years did not recognize ablution when they were praying. The method of developing multimedia systems by Luther-Sutopo is one of the system development methods used by multimedia application developers. Therefore it will be built an Android operating learning media that uses Adobe Flash technology to display an animated image, motion, and audio in a 2-dimensional form. This learning media will display 2-dimensional objects of ablution movements, namely intentions, washing both feet and prayer after ablution, and prayer movements from beginning to end and added a few daily prayers. The results of this study are in the form of learning applications for ablution and five-time prayer based on Android. In this application using elements of text, images, animations, and sounds to attract and make it easier for children to remember lessons on how to perform ablution and prayer and various kinds of daily prayers.